Effect of Home Enteral Nutrition on Nutritional Status, Body Composition and Quality of Life in Patients With Malnourished Intestinal Failure - Gao, Xuejin; Zhang, Yupeng; Zhang, Li; Liu, Sitong; Liu, Hao; Zhou, Da; Li, Jieshou; Wang, Xinying (Frontiers in Nutrition, 2021)
Background: The ultimate goal of intestinal failure (IF) management is to maintain optimal nutritional status, improve the quality of life (QoL), and promote intestinal adaptation. Enteral nutrition support is safe and effective in patients with IF and plays a central role in the management of patients with IF. The purpose of this study was to evaluate the effect of home enteral nutrition on nutritional status, body composition (BC), QoL and other clinical outcomes in malnourished patients with intestinal failure. Methods: This prospective observational study included 166 malnourished patients with intestinal failure presented to Jinling Hospital from January 2016 to October 2018. All patients were supported with home enteral nutrition after discharge. We evaluated clinical outcomes, including nutritional status, BC, phase angle (PhA), QoL, mortality, gastrointestinal complications related to enteral feeding, and other clinical outcomes at 1, 3, and 6 months after discharge. Results: Body weight, BC, and other nutritional parameters were maintained or significantly increased during the period of home enteral nutrition after discharge (p<0.01). Especially, the quality of skeletal muscle mass in body composition was significantly improved (p<0.01). SF-36 quality of life scores was significantly improved (discharged at 6 months: reported health transition 40.7±12.1 vs. 69.3±16.3, p<0.01). There were no differences between hospital and out of hospital with respect to tube-related or gastrointestinal complications. Advanced age, disease type, and poor nutritional status were risk factors for poor clinical outcomes. Conclusions: Home enteral nutrition support is effective for malnourished patients with intestinal failure. It improves nutritional status, BC, PhA, and QoL.